Proses Pembelajaran Pendidikan Agama Islam Pada Sekolahalam Minangkabau di Kota Padang - Sari, Widia Wahana; Alfurqan, Alfurqan; Arsiyah, Arsiyah (Universitas Islam Negeri Raden Intan Lampung, 2021)
Islamic Religious Education Learning is usually carried out in a formal education environment, but in fact the non-formal education environment has a major influence on the achievement of Islamic Religious Education learning such as in Minangkabau natural schools. This study aims to find out as well as explore how the implementation of Islamic Religious Education learning at the Minangkabau Natural School. This study uses a qualitative research method with a case study approach (case study design). Qualitative data sources were taken to seventeen informants, using purposive sampling technique through in-depth interviews and analyzed using document analysis. All informants are people who are directly involved in learning in Minangkabau natural schools. Overall, the results of the study indicate that there are five learning processes of Islamic Religious Education carried out in Minangkabau natural schools. The five processes are: i) determining the school curriculum, ii) compiling a learning syllabus, iii) preparing learning materials, iv) preparing learning media facilities, and v) determining the use of learning approaches and methods. The results of this study can be used as initial data for future researchers in examining this problem in different contexts and issues.